Understanding Analysis of Muslim Society About Sharia Banking - Akbar, Aidil; Hsb, Mhd. Aziz Alfarisi; Lestari, Dini (IKAMAS: Manajemen Pendidikan Islam, 2023)
Islamic banking or in the international world is commonly referred to as Islamic banking or also known as interest-free banking. The use of the word sharia in the word sharia banking cannot be separated from the origins of the sharia banking system. This is motivated by the pressure on Muslim economists and banking practitioners who want financial services that accommodate financial transactions that run straight with sharia principles in Islam and also moral values. The main factor arises from the practice of prohibiting usury, maysir activities, and also gharar activities. Therefore, Muslim economists and Muslim banking practitioners have created Islamic financial institutions based on the Al-Quran and As-Sunnah whose activities continue to grow. The purpose of this study was to describe the public's understanding of the development of Islamic banking in Environment II, Tanah Seribu Village, South Binjai District, Binjai City. In this study, researchers used qualitative research. The methodology used is descriptive qualitative methodology. In this case it is used to describe the extent of understanding of the Muslim community in the Tanah Seribu sub-district about Islamic banking. From the results of interviews conducted with 6 members of the Muslim community in the land of a thousand cities, Binjai. That the awareness of Islamic banks in the city of Binjai is quite high. This is based on the 6 respondents who were studied, all of whom knew about the existence of Islamic banking in the city of Binjai. the researcher concludes that many people in the country of a thousand know Islamic banking, but many also only know but do not use products from Islamic banking. Only a few respondents use products and services from Islamic banking. However, the understanding of the people of Tanah Seribu is quite high about Islamic banks, this is because all respondents answered that Islamic banks are Islamic banks that do not use interest and do not make a lot of deductions.